Profiles of local growth and industrial change: Facts and an Explanation - Wolfgang Dauth; Jens Südekum (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper we take a detailed look at the sectoral anatomy of regional growth in German regions over the period 1978-2008. In the aggregate, the German economy is characterized by a secular decline of the manufacturing sector and a rise of the modern service economy. This trend of structural change (Petty s law) by no means occurs uniformly across space, however. Some regions exhibit this trend even at an accelerated pace, while other regions develop their local economic structures against the trend and expand their manufacturing bases. We first develop a novel empirical approach that allows us to categorize all German regions into one out of three groups with pro-trend , anti-trend or featureless regional growth. Afterwards we show that the differential exposure to international trade is an important cause of the divergent patterns of local industrial change.
Keywords: R11; R12; F16; 330